Chemical Composition GC/MS analysis, antioxidant and Antimicrobial Activity of Hibiscus, Baobab, and Buckhorn Seed Oil’s - Eisa, Nidal; Mohamed Masaad, Ali; Abdallah Ahmed, Ayman; Abubaker , Alyaa; Eisa, Alaa; Ahmed, Miska (Universitas Islam Indonesia, 2026)
This study explores the chemical composition and bioactive potential of Baobab, Hibiscus, and Buckthorn seed oils, focusing on their antioxidant and antimicrobial activities for cosmetic and functional food applications. GC/MS analysis revealed distinct profiles: Hibiscus oil was rich in 10(E),12(Z)-conjugated linoleic acid (32.87%) and cis-13-Octadecenoic acid (31.54%), Baobab oil contained high levels of cis-Vaccenic acid (24.59%) and n-Hexadecenoic acid (17.57%), and Buckthorn oil was characterized by significant concentrations of gamma-Sitosterol (12.78%) and gamma-Tocopherol (11.5%). The antioxidant capacity, measured using the DPPH assay, showed Buckthorn oil as the most active (IC₅₀ = 7.2 mg/mL), followed by Hibiscus (IC₅₀ = 11.7 mg/mL) and Baobab (IC₅₀ = 24.9 mg/mL), highlighting their potential as natural antioxidants, with Buckthorn oil demonstrating superior efficacy. Antimicrobial testing against Staphylococcus aureus, Escherichia coli, and Candida albicansrevealed limited activity. Baobab and Buckthorn oils showed weak inhibition against S. aureus (9.3 mm and 9.0 mm, respectively). In contrast, Hibiscus oil had no effect, and none of the oils inhibited E. coli or C. albicans. One-way ANOVA confirmed no significant differences in inhibition zones against S. aureus (p = 0.204), indicating that the antimicrobial effects are weak and not statistically meaningful. These findings demonstrate that while the tested oils have strong antioxidant potential, particularly Buckthorn oil, their antimicrobial activity in crude form is limited. Future studies incorporating MIC determination and formulation optimization could enhance their practical applications in cosmetics, pharmaceuticals, and functional foods.